High-intensity interval training in middle-distance NCAA Division I 800/1500m collegiate athletes - Price, F. G.; Smith, J. E. W.; Turner, A. J.; Krings, B. M.; Waldman, H. S.; Chander, H.; Knight, A. C.; McAllister, M. J. (International Journal of Kinesiology & Sports Science, 2020)
Background: High-intensity interval training (HIIT) has grown in popularity, with studies demonstrating improvements in aerobic and anaerobic performances within Sedentary and Recreationally active adults. Little research has been comprised on collegiate, middle-distance runners (800m/1500m). Objective: This research study aimed to investigate the impact of four-weeks HIIT cycling training on collegiate 800/1500m runners performance, and determine whether HIIT can be used as an alternative training method for student athletes. Methods: Twelve middle-distance runners were recruited, with six athletes completing the intervention. Athletes completed pre-testing, which included a 1500m time trial, a GXT, stride length and frequency measurements, and MVIC, using Biopac electromyography (EMG). After pre-testing, athletes completed four weeks of HIIT twice per week. The HIIT consisted of four 20-second bouts with 4 minutes recovery. Following the completion of the training intervention, post-testing was performed for all measures. A paired t-test was used to determine differences between pre- and post-performance tests. An ANOVA was used to determine changes in heart rate and RPE during the GXT. Results: Significant changes were demonstrated between the pre- and post-muscle activation tests of the quadriceps (p=0.05). Significant changes were seen with both HR (p<0.05) and RPE (p<0.05) throughout the GXT. No other significant differences were demonstrated between pre- and post-performance tests, concluding four-weeks HIIT does not alter 800/1500m performance. Conclusion: From the results of this study, HIIT could be used as an alternate method for training for 800/1500m runners. Further reasearch should be conducted toto further understand the impacts of HIIT on middle distance athletes.